“Ways of integrating e-tandem mode in the language curriculum in the English career at Technical University of Cotopaxi” - Zuña Tenemaza, Mirian Sofia (2022)
E-tandem mode is a language learning method where students of different mother tongues can practice and improve a language. It has been implemented in some universities providing students with an innovative way of learning a language. E-tandem has helped students to develop their communicative and cultural competence. Despite these benefits, the Technical University of Cotopaxi (UTC) does not have this modality in the English career. Thus, it is important to integrate e-tandem into the language curriculum since it would allow pre-service English teacher to enhance their pedagogical skills. Whereby, this research study aimed at analyzing the different ways of integrating e-tandem mode in the language curriculum in the English career at UTC, because of their important experiences with this mode of language learning. The qualitative methodology was followed as well as interviews and focus groups techniques. The participants were eleven EFL pre-service teachers: two were in their fifth semester, four in their sixth semester, one in his seventh semester, and four in their eighth semesters as well as two professors. The criteria to select the participants was that they had participated in the e-tandem pilot project carried out in 2020-2021 at UTC. The bottom-up approach was used to analyze the collected data from participants’ opinions. In addition, the Academic Regime Regulations of Ecuador were analyzed, to have a better perspective of the e-tandem curriculum inclusion. The analysis of the data suggested that the e-tandem can be integrated into the curriculum of the English career in two ways: as a component of a subject and as pre-professional practice. As a component of a subject, giving rewards (scores) when learners participate in sessions. As a pre-professional practice activity in which students of the last career levels can participate as tutors in the e-tandem interactions. Moreover, as a part of the results, it can be said that if this mode is integrated into the curriculum, it would be able to minimize technological problems, have the e-tandem sessions in the schedule, and monitor students’ performance. It is recommended to apply pilot plans in the English career with the application of the e-tandem sessions in the two modalities, to then be subjected to an evaluation and thus know which of them would give better results.